PENGEMBANGAN KOSAMI (KOMIK SAKU MATEMATIKA) BAGI SISWA KELAS VII SMP NEGERI 7 TARAKAN - Syafitri Eva Susanti; Hariaty Hamid; Nurmala R (Mathematics Education And Application Journal (META), 2019)
The development model used is the Borg and Gall model of Sugiyono modification. In the Borg and Gall model, the Sugiyono modification consists of 10 stages, namely Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Testing, Product Revision, Usage Testing, Product Revision and Mass Production. The media testing phase is done through 2 stages, namely the assessment of experts and user response. In the assessment of experts validated by material experts, media experts and linguists. While the user response was tested by 30 students and 2 mathematics teachers. The results of analysis shows that the kosami product developed based on validation by material experts obtained a feasible category with a percentage of 79.68%, media experts obtained the category of Very Eligible with a percentage of 92.72% and linguists obtained the Very Eligible category with a percentage of 83.33%.While the result of research in the field by the response of teacher user obtained a percentage of 75% with a Very Practical category, responses of student users obtained by 87,33% with a Very Eligible category, and responses of student users obtained by 90,67% with a Very Practical category . Because it has fulfilled the feasible and practical requirements of a Kosami learning media consisting of aspects of material feasibility, media feasibility, feasibility of language use, and practicality of user response, the kosami can be used as a feasible and practical learning media for students of clas VII SMP Negeri 7 Tarakan on  Number Material.